2001
DOI: 10.1111/j.1751-3928.2001.tb00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐sulphate Type Alteration and Mineralization in the Desmos Caldera, Manus Back‐arc Basin, Papua New Guinea

Abstract: Abstract:The Onsen acid-sulphate type of mineralization is located in the Desmos caldera, Manus back-arc basin. Hydrothermal precipitates, fresh and altered basaltic andesite collected from the Desmos caldera were studied to determine mineralization and mobility of elements under seawater dominated condition of hydrothermal alteration.The mineralization is characterized by three stages of advanced argillic alteration. Alteration stage I is characterized by coarse subhedral pyrophyllite with disseminated anhedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Several outcrops of heavily bleached rocks cemented with native sulfur were observed near active vents, presumably reflecting advanced argillic alteration by acid-sulfate type fluids (Brimhall and Ghiorso, 1983;Gena et al, 2001;Binns et al, 2007). However, no 'white smoker activity' similar to the DESMOS caldera site (Gamo et al, 1997;Gamo et al, 2006) has been observed anywhere on Pual Ridge.…”
Section: Pacmanus and Northeast Pualmentioning
confidence: 98%
See 1 more Smart Citation
“…Several outcrops of heavily bleached rocks cemented with native sulfur were observed near active vents, presumably reflecting advanced argillic alteration by acid-sulfate type fluids (Brimhall and Ghiorso, 1983;Gena et al, 2001;Binns et al, 2007). However, no 'white smoker activity' similar to the DESMOS caldera site (Gamo et al, 1997;Gamo et al, 2006) has been observed anywhere on Pual Ridge.…”
Section: Pacmanus and Northeast Pualmentioning
confidence: 98%
“…In contrast to MOR settings, where CO 2 is the dominant volatile degassed, the exsolution of large quantities of H 2 O and CO 2 from water-rich silicic magmas can be accompanied by acid-volatile species such as SO 2 , HCl and HF. Subsequent entrainment of water-rich magmatic fluids into existing hydrothermal circulation cells could substantially lower pH, thereby influencing the transport of dissolved metals and styles of crustal alteration (Gamo et al, 1997;Gena et al, 2001;Gamo et al, 2006;. Moreover, magmatic fluids have long been proposed as an additional source of economically important metals (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a fundamental question about mass flux at Earth's surface is the influence of subducting materials and magmatic volatiles. Extremely acidic fluids affected by magmatic volatiles raise the solubility of metals and mobilize them from rocks to fluids (Gamo et al 1997b(Gamo et al , 2006Gena et al 2001;Yang and Scott 2006). This aspect of the metal supply may have a great influence on Fe-utilizing ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrite precipitated within this environment is a product of reaction between H 2 S derived from magmatic SO 2 disproportionation and Fe-bearing minerals within the host-rock. Although pyrite precipitation likely occurs at greater depths beneath the seafloor within more reducing fluids, disseminated and veined pyrite has been described in advanced-argillic alteration assemblages at seafloor at both DESMOS and SuSu Knolls Gena et al, 2001;. shift to more oxidizing conditions (i.e., S0 4 -dominant) can result from continued degassing of SO 2 and alteration of crustal rocks that exhausts the capacity of the rock to buffer H 2 S/SO 4 2 , similar to supergene alteration processes described for continental magmatic-hydrothermal processes (Giggenbach, 1997).…”
Section: Remobilization Of Previously Deposited Metal Sulfidesmentioning
confidence: 99%